Pengembangan Aplikasi Dashboard Pasien Rawat Inap Pada Rumah Sakit XYZ Menggunakan Framework Laravel - Sekar, Agung; Yuningsih, Lilis (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 12 of 2013 in article 20 paragraph 1 explains that patient beds are a basic element in the quality of inpatient health service provision. One of the activities that can be carried out by hospitals with the current information system includes optimizing the information system to obtain accurate information about the availability of patient rooms and information on occupied bedrooms and the total temporary bill of patients while in inpatient care. Therefore, the existence of bed management is very important for the quality of service to patients. In one of the private hospitals in Denpasar city, it has implemented an information system related to daily visits of outpatients, but the hospital still cannot optimally utilize the system because it can only display information on outpatient visits. In the current research, the development of this dashboard application will be equipped with several inpatient visit modules which will be able to display information related to the number of inpatients currently being treated, empty beds, patient deposits and related total patient temporary treatment bills. It is hoped that this application can assist hospital management in monitoring the number of daily visits of outpatients and inpatients so that it can be utilized for the business needs of the hospital.